Method for determination of discharge capacity of automatic steam traps - British Standards Institution (London BSI, 1990)
Steam traps, Steam engineering, Traps (separators), Automatic, Flow rates, Test equipment, Testing conditions, Mathematical calculations, Flow measurement
Replaced By BS EN 27842:1991, ISO 7842:1988
Superseded, Withdrawn
Cross References BS 791, BS 1042:Section 1.1, BS 5074, BS 5844, BS 6023, BS 6199:Part 1, ISO 652, ISO 6704, ISO 6948
International Relationships ISO 7842
Keywords: Automatic steam traps -- Standards